Two new species of the genus Deltophora Janse, 1950 (Lepidoptera: Gelechiidae) - Li, Houhun; Wang, Zhibo; Sattler, Klaus (Zootaxa, 2016)
Two Chinese species of the genus Deltophora Janse (Lepidoptera: Gelechiidae), both in obligate mutualism with the plant genus Phyllanthus L. (Phyllanthaceae), are newly described: Deltophora phyllanthicella Li et Sattler sp. n., from Hainan, a pollinator of its larval host Phyllanthus rheophyticus Gilbert et Li; Deltophora polliniferens Li et Sattler sp. n., from Guangdong, a pollinator of its larval host Phyllanthus cochinchinensis (Lour.) Spreng. The adults and the male and female genital structures of both species are described and illustrated. The presence of a fully developed 1st instar larva in the female abdomen of Deltophora phyllanthicella is recorded as the first such case in Gelechiidae.